Understanding giftedness : a guide for parents and educators (Understanding atypical development., 2020)
This concise, accessible guide explores the different models behind the concept of giftedness, examining the criteria for evaluating and identifying gifted children, in order to provide a deeper understanding of the lives of children and young people with high cognitive potential. It offers practical advice to parents and teachers, highlighting common queries and misconceptions and presenting evidence-based suggestions for management methods. Key topics covered include the difference between being gifted and talented, how to identify a gifted child, neurological differences between gifted children and their peers, dealing with perfectionism, and the best ways to parent and teach a gifted child. Avoiding prescriptive rules, the authors emphasise the importance of knowing and understanding the individual child whilst utilising research around giftedness to promote the best possible outcomes. Illustrated with case studies of student and teacher perspectives, the book offers an inclusive perspective and practical strategies, whereby the development of individual potential is viewed not only as a way to promote the psychological well-being of the individual but also as an opportunity and benefit for society. Understanding Giftedness is essential reading for parents and caregivers, as well as practitioners in clinical and educational psychology, counselling, mental health, nursing, child welfare, public healthcare and those in education who want to help young people develop their talents and achieve their full potential.